Demographic Factors’ Moderating Effects on University Students’ Brand Loyalty towards Mobile Service Operators in Eastern Region of Thailand - Lu, Fei; Phienphisai, Chadillada (Journal of Applied Economics and Management Strategy, 2022)
ABSTRACT Telecommunication industry plays a significant role in any country’s economic sector and will often face fierce competition in mobile service market. In order for business to survive and sustain, mobile service providers must be creative and adaptable so as to avoid losing customers to competitors. Understanding essential factors that influence customer’s behavior will assist mobile service operators establish brand loyalty and achieve long-term profitability. This research study aims to investigate and provide the imperative information regarding the contributing factors of university students’ brand loyalty towards mobile service and the moderating effects of university students’ demographic characteristics on such relationship in the eastern region of Thailand. The population for this study is the currently enrolled students in selected Thai universities during this research study. The sample size in this study is 698 students who are studying in three selected universities from Chonburi province in the eastern region of Thailand. Research participants were chosen by using purposive sampling method, and research instrument applied in data collection is questionnaire with reliability value (Cronbach’s Alpha) equals to 0.914. Factor analysis, Structural equation modeling (SEM) and multi-group SEM are employed to investigate causal relationship and moderating effects. Research results show that four factors: (1) perceived value, (2) corporate image, (3) perceived quality, and (4) perceived inconvenience are positively correlated with university students’ brand loyalty towards mobile service operators in Thailand. In terms of the moderating effect, four proposed demographic variables (age, income, residency and number of children) are found significant. Therefore, from findings of this research, mobile service providers in Thailand are advised to efficiently optimize corporate resources into developing service packages with better quality and value, as well as improving corporate’s public image in order to enhance university students’ brand loyalty. The confirmed influencing demographic moderators suggest mobile service operators should economically allocate financial resource on building long-term student customer’s loyalty of specific demographic groups instead of all student groups.